Main analytical techniques used for elemental analysis in various matrices - Helaluddin , Abul Bashar Mohammed; Khalid , Reem S.; Alaama, Mohammed; Abbas, Syed Atif (Pharmacotherapy Group, Faculty of Pharmacy, University of Benin, 2016)
Heavy metal pollution is a serious environmental problem. The presence of such metals in different areas of an ecosystem subsequently leads to the contamination of consumable products such as dietary and processed materials. Accurate monitoring of metal concentrations in various samples is of importance in order to minimize health hazards resulting from exposure to such toxic substances. For this purpose, it is essential to have a general understanding of the basic principles for different methods of elemental analysis. This article provides an overview of the most sensitive techniques of elemental analysis such as atomic absorption/emission spectrometry, mass spectrometry, x-ray fluorescence, voltametry, and nuclear techniques. In addition, the article addresses some applications in a range of sample matrices.